2022
DOI: 10.1186/s13195-022-00979-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thioredoxin-80 is associated with age, ApoE4, and neuropathological biomarkers in Alzheimer’s disease: a potential early sign of AD

Abstract: Background Thioredoxin-80 (Trx80) is a cleavage product from the redox-active protein Thioredoxin-1 and has been previously described as a pro-inflammatory cytokine secreted by immune cells. Previous studies in our group reported that Trx80 levels are depleted in Alzheimer’s disease (AD) brains. However, no studies so far have investigated peripheral Trx80 levels in the context of AD pathology and whether could be associated with the main known AD risk factors and biomarkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Thus, using this human BBB model, we incubated TNF-α and/or IL-1β in the abluminal compartment (brain side) at 10 ng·mL −1 for 24 h to mimic CNS inflammation. The used concentrations of 10 ng·mL −1 for TNF-α or IL-1β to mimic inflammation were selected based on different studies using in vitro BBB models [ 25 , 27 , 30 , 31 , 32 , 33 ], despite serum concentration described to be in the pg·mL −1 range [ 34 ]. Furthermore, the use of the same concentration between TNF-α or IL-1β in our study stems from the work of Grammas and Ovase, who demonstrated that the secretion of these two proinflammatory cytokines is equivalent (almost 30 pg·mL −1 ) in the brain microvessels of AD patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, using this human BBB model, we incubated TNF-α and/or IL-1β in the abluminal compartment (brain side) at 10 ng·mL −1 for 24 h to mimic CNS inflammation. The used concentrations of 10 ng·mL −1 for TNF-α or IL-1β to mimic inflammation were selected based on different studies using in vitro BBB models [ 25 , 27 , 30 , 31 , 32 , 33 ], despite serum concentration described to be in the pg·mL −1 range [ 34 ]. Furthermore, the use of the same concentration between TNF-α or IL-1β in our study stems from the work of Grammas and Ovase, who demonstrated that the secretion of these two proinflammatory cytokines is equivalent (almost 30 pg·mL −1 ) in the brain microvessels of AD patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…P-tau/Aβ42 ratio was preferentially selected as a specific marker for Alzheimer’s disease instead of individual markers, as it has been shown that the ratio is superior in assessing amyloid pathology. 28 SNAP-25 was the only synaptic marker that differed between the clinical groups in our material and it has been shown to possess the best discriminatory power to distinguish Alzheimer’s disease from non-Alzheimer patients compared to other synaptic biomarkers, 25 therefore we selected it as a synaptic dysfunction outcome measure. The results of the analysis are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…24 TRX-80 was quantified by an in-house sandwich ELISA, as previously published. 10,25 All samples were tested in duplicate, and the average was considered for the statistical analyses. To assess for inter-assay variability, three same CSF samples were assayed in every plate, for each biomarker analysis.…”
Section: Csf Biomarkers Agt Enpp-2 Trx-1 Trx-80 and Neurofilament Lig...mentioning
confidence: 99%
“…The average age was 68 years (SD 9.42), and the sex distribution was 23/77% men/women (n = 6/20) in the control group, and 36/64% men/women (n = 10/18) in the AD group. The clinical and diagnostic data of the GEDOC cohort are described in detail in Goikolea et al (2022) and Rosenberg et al (2019).…”
Section: Quanti Cation Of Sirt2 In Human Serum Samplesmentioning
confidence: 99%